Analysis of Student Errors in Solving Mathematical Induction Problems in Online Learning - Sukma Cipta, Eliva; Maya, Rippi; Suryadi, Didi; Prabawanto, Sufyani (KnE Social Sciences, 2024)
The research aims to analyze student errors in solving math induction-proof problems during online learning in the Covid 19 era. This was a qualitative research with a case study approach. This research was conducted at the Mathematics Education Study Program of UIN Sunan Gunung Djati Bandung in the academic year 2020/2021, and the subjects of this study being students of semester V Class 2018. The instrument in this study was a test, and data analysis were done using qualitiative anlysis. The results showed that the types of errors experienced by students in working on mathematical induction problems are conceptual errors and procedural errors. Keywords: online learning, solving mathematical induction problems, student errors